Ophthalmic Artery Occlusion From Injection of Heroin Into the Forehead. (July 2019) - Ploysangam, Pimpiroon; Koreishi, Faruk; Lema, Gareth M.C.
Purpose: To report a case of ophthalmic artery occlusion after injection of heroin into the forehead. Methods: Retrospective case report. Results: A 27-year-old patient with a history of intravenous heroin abuse presented with a left ophthalmic artery occlusion after attempting to inject heroin into a vein in her forehead. Exam was significant for diffuse retinal edema, disc edema, disc hemorrhage, and diffuse retinal hemorrhages. Findings were also noted in the widefield image, optical coherence tomography, and optical coherence tomography angiography of the retina. Conclusions: This patient suffered from a severe form of talc retinopathy resulting in an ophthalmic artery occlusion after injecting heroin into her forehead. To our knowledge, this is the first instance of combined ophthalmic artery occlusion and talc retinopathy resulting from intentional injection into a superficial facial vein.